Public Health Reviews - Paccaud, Fred; Chambaud, Laurent
Public Health Reviews (PHR) is the official journal of the Association of Schools of Public Health in the European Region (ASPHER). It is a multi-disciplinary journal dedicated to publishing topics of current importance to public health. The journal promotes public health knowledge and best practices, placing a special emphasis on the integration of state of the art information and translational issues, interdisciplinary approaches, innovations, and emerging public health concerns. The scope of the journal is global, but special emphasis is placed on Europe and issues that impact and speak to public health in the European Region. The journal publishes thematic series of high quality review articles on key topics in public health that aim to inform public health practitioners, teachers, students and policymakers.  We present historical and contemporary reviews to emphasize new possibilities for public health, to translate research into recommendations for best practices in the real world and to promote discussion in the public health community. Articles are commissioned and submissions are welcomed to ensure comprehensive treatment of the topics at hand. Thematic series address current compelling concerns and challenges to public health and wellbeing, such as migrant and minority health, climate change, law and patient care, disease screening, ethics in public health, human rights, new issues in public health education and the human life course. Public Health Reviews welcomes review papers, commentaries, case studies and opinion pieces that speak to emergent public health concerns. We look for comprehensive synthesis of state of the art knowledge that is translated into real world recommendations and solutions. Publications are not limited to Europe, but as the official journal of ASPHER, we encourage the submission of articles from all countries within the European Region, while open to global health issues. .